Minireview: Prospect of Doxycycline in Systemic Lupus Erythematosus Treatment - Niken Indriyanti; Joewono Soeroso (Journal of Tropical Pharmacy and Chemistry, 2019)
Doxycycline has non-antibiotic effects which are necessary for lupus treatment, such as immunosuppressive, anti-inflammatory, and anti-depressive effects. This widely used drug is a promising one to be developed as lupus drug since doxycycline has no data of its microbial resistance and it is safe for maternity. The other benefit is that doxycycline has lower side effects than the current drugs for lupus treatment. It gives excellent chances for women with lupus to be pregnant and have healthy babies. This article contains the compilation data of doxycycline target sites beyond its beneficial activities for lupus and also its limitations. Finally, this data will be a background for doxycycline in lupus drug development.